Analisis Tingkat Kerusakan Kemasan Mie Instan Goreng Menggunakan Metode Six Sigma dan FMEA Pada PT. Karunia Alam Segar - Aldila Syafa Salsa Sabillah; Yanuar Pandu Negoro; Hidayat Hidayat (Universitas Islam Raden Rahmat, Malang, 2024)
PT. KAS or known as PT. Karunia AIam Segar is one of the F&B companies that produces products in the form of instant noodles. In the production process, PT. KAS has several divisions to process raw materials into the final product, namely instant noodles which have been packaged and given additional spices according to the type of taste. Of the many processes that go through, this company's final product results in defective products such as pieces of noodles, crushed spices, squashed noodles, cuts, temperature and/or joints, misprinted expiry dates, and seasoning oil leaking in the packaging. From the problems obtained, the author carried out research using the Six Sigma and FMEA methods with the aim of minimizing the number of variations in product defects. Based on the results of data processing on fried instant noodle packaging defects, it has a six sigma value of 4.96. Meanwhile, the highest RPN value for temperature and/or connections due to human factors (man) was 504, and the highest RPN value for oil leaks in packaging due to human factors (man) was 567.